Case Report: Maternal near-miss—recovery from refractory septic shock with multiple organ dysfunction secondary to acute pyelonephritis in pregnancy - Chen, Hong; Huang, Ziyu; Chen, Guihua; Tang, Yaling; Yang, Dongxia (Frontiers in Medicine, 2025)
BackgroundUrinary tract infections during pregnancy represent a significant clinical concern, posing considerable risks to both maternal and fetal health. The physiological changes associated with pregnancy increase the susceptibility to infections, with an estimated 15 to 20% of acute pyelonephritis cases potentially progressing to bacteremia, particularly in the context of urinary stones. The onset of sepsis may lead to septic shock and multiple organ dysfunction, adversely affecting the kidneys, liver, lungs, heart, and central nervous system. Recent research into the pathogenesis of sepsis has provided insight into how inflammation and the activation of immune responses can induce abnormalities in circulatory function, subsequently triggering systemic ischemia and resulting hypoxia.Case presentationA 42-year-old pregnant woman presented with acute renal colic and fever, leading to the diagnosis of nephrolithiasis, hydronephrosis, and acute pyelonephritis. The clinical condition rapidly deteriorated, evolving into uroseptic shock, cardiogenic shock, and multiple organ dysfunction syndrome. This alarming progression necessitated her admission to the intensive care unit, where she received aggressive treatment interventions, including extracorporeal membrane oxygenation (ECMO), an intra-aortic balloon pump (IABP), and continuous renal replacement therapy (CRRT). Remarkably, these life-saving measures proved successful. After nine days in intensive care, she fully recovered and was discharged.ConclusionThis case study explores three critical clinical challenges: strategies for early identification of high-risk pregnant women for sepsis; optimal timing for interventions in obstructive urinary tract infections to prevent septic shock and multi-organ dysfunction; and the implementation of mechanical circulatory support. The circulatory support protocol highlights the importance of personalized interventions in complex medical scenarios.